Operator on types of numberings - Mustafa, M. (Nazarbayev University, 2014)
The reductions constructed permit to give various alternative proofs to known results about d.r.e. and, in general,a-r.e. numberings. For example, one can show that for every recursive ordinal a which is not an w-power and every Rogers semilattice of r.e. sets, the corresponding semilattice is also realized within the a-r.e. numberings.
Keywords: numberings; types; semilattices; constructed permit; elements